Contagion of currency crises: Some theoretical and empirical analysis - Alexander Karmann; Oliver Greßmann; Christian Hott (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2002)
This paper investigates contagion effects. In a model with highly and lowly informed investors we show that a currency crisis in one country can trigger a crisis in another country. Portfolio losses of the highly informed investors in one country will force them to withdraw capital from the other country. The behavior of the lowly informed investors multiplies this effect and the other country becomes more and more vulnerable. In the empirical part we focus on the Asian crisis (1997/98). Using a LOGIT approach we can show that contagion, in the sense of a crisis not explainable by economic fundamentals but by exchange rate losses resulting from investment in other countries, seems to have caused the currency crises of the Philippines and especially of Singapore.
Keywords: F3; F4; 330; Contagion; Currency crises; Asian crisis; Währungskrise; Portfolio-Investition; Unvollkommene Information; Kapitalmobilität; Internationaler Preiszusammenhang; Zwei-Länder-Modell; Schätzung; Theorie; Asien